Tanda-Tanda Perundungan dalam Film “Are You Okay?” - Osvaldo, Juan; Pandrianto, Nigar (Koneksi, 2023)
A film is a moving image or so-called audio-visual media. Film can be used as a medium for conveying messages, and films currently act as a popular medium for conveying messages very effectively. Every film is always built with many marks. These signs have the meaning that the filmmaker wants to convey. In this research, the researcher wants to know and describe the signs of bullying in the short film "Are You Okay?". This study uses the concept of the film, bullying, the spiral of silence theory and Charles Sanders' model of semiotics. The subject of this research is scenes in the short film “Are You Okay?” who have signs of bullying, and the object of this research is the signs of bullying in the short film "Are You Okay?". The research method used by researchers is a qualitative research method. The theory used in this study is Charles Sanders Peirce's semiotic theory. The author uses document analysis and literature study to gather the required information. The results of this study indicate that there are signs of bullying in the short film "Are You Okay?" through a number of scenes in the form of representamen, objects, and interpretants. Film adalah gambar yang bergerak atau biasa disebut media audio visual. Film dapat dibuat sebagai media untuk menyampaikan sebuah pesan, film pada saat ini berperan sebagai media popular untuk menyampaikan pesan dengan sangat efektif. Setiap film selalu dibangun dengan banyak tanda. Tanda-tanda tersebut memiliki makna-makna yang ingin disampaikan oleh pembuat film. Peneliti ingin mencari tahu serta mendeskripsikan tanda-tanda perundungan yang terdapat dalam film pendek “Are You Okay?”. Penelitian ini menggunakan konsep film, perundungan, teori spiral of silence dan semiotika model Charles Sanders. Subjek dari penelitian ini adalah adegan-adegan dalam film pendek “Are You Okay?” yang memiliki tanda-tanda perundungan dan objek dari penelitian kali ini adalah tanda-tanda perundungan pada film pendek “Are You Okay?”. Metode penelitian yang digunakan oleh peneliti adalah metode penelitian kualitatif dengan semiotika Charles Sanders Peirce. Penulis menggunakan analisis dokumen dan riset perpustakaan dalam mengumpulkan informasi yang dibutuhkan. Hasil penelitian ini menunjukkan bahwa terdapat tanda-tanda perundungan dalam film pendek “Are You Okay?” melalui sejumlah scene dalam bentuk representamen, objek, dan interpretan.